The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1990
DOI: 10.1182/blood.v75.11.2164.bloodjournal75112164
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative and quantitative analysis of the activation and inactivation of protein C in vivo in a primate model

Abstract: A model of Protein C (PC) activation in vivo was used to investigate the complexing of activated PC (APC) with its plasma inhibitors, PC inhibitor (PCI) and alpha 1-antitrypsin (alpha 1AT). Chimpanzees were infused with a bolus of activated factor X (F.Xa) together with vesicles of phosphatidylcholine and phosphatidylserine (PCPS). Pre- and post-infusion plasma samples were analyzed using enzyme linked immunosorbent based assays (ELISA) for PC and APC complexes, and immunoblotting of PC from nondenaturing poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

1990
1990
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 0 publications
1
19
0
Order By: Relevance
“…All assays were performed in the investigators' laboratories either by ELISA: FV antigen [coefficient of variation (CV) 5.8%][21], FVIII antigen (CV 7.8%), FIX antigen (CV 10%), VWF (CV 3%) [22], protein Z (CV 6.5%) [24], ZPI (CV 7.2%) [24], APC–α1AT complex (CV 12.4%) [25] and APC–PCI complex (CV 11.7%) [25], or radioimmunoassay: prothrombin (CV 8%) [26], antithrombin (CV 5%) [27,28], protein S (CV 9.8%) [29], F1.2 (CV 8%) [28], PCP (CV 14%) [28] and FPA (CV 8%) [28], the Clauss method for fibrinogen (CV 1.7%) [30,31] using the ST4 instrument (Diagnostica Stago, Parsipanny, NJ, USA), a clot‐based functional assay for protein C: (CV 5.5%) [20,23] or micro latex bead agglutination for d ‐dimer (CV 9.2%) (Biomerieux, Durham, NC, USA) [32,33].…”
Section: Methodsmentioning
confidence: 99%
“…All assays were performed in the investigators' laboratories either by ELISA: FV antigen [coefficient of variation (CV) 5.8%][21], FVIII antigen (CV 7.8%), FIX antigen (CV 10%), VWF (CV 3%) [22], protein Z (CV 6.5%) [24], ZPI (CV 7.2%) [24], APC–α1AT complex (CV 12.4%) [25] and APC–PCI complex (CV 11.7%) [25], or radioimmunoassay: prothrombin (CV 8%) [26], antithrombin (CV 5%) [27,28], protein S (CV 9.8%) [29], F1.2 (CV 8%) [28], PCP (CV 14%) [28] and FPA (CV 8%) [28], the Clauss method for fibrinogen (CV 1.7%) [30,31] using the ST4 instrument (Diagnostica Stago, Parsipanny, NJ, USA), a clot‐based functional assay for protein C: (CV 5.5%) [20,23] or micro latex bead agglutination for d ‐dimer (CV 9.2%) (Biomerieux, Durham, NC, USA) [32,33].…”
Section: Methodsmentioning
confidence: 99%
“…Because both APC–PCI and APC–α l AT complexes are observed in plasma of patients with intravascular coagulation, α l AT is also considered a secondary physiological APC inhibitor [55,62,63]. In experiments using primate models, soon after injection of APC, the APC–PCI complex appeared first, and then, when free PCI was decreased by consumption, APC‐α l AT and APC‐α 2 macroglobulin complexes appeared [64,65]. In thrombotic patients treated with heparin, the APC–PCI complex was predominantly observed [66].…”
Section: Physiological and Pathological Functions Of Pcimentioning
confidence: 99%
“…reported that urinary PCI prevents LPS‐induced disseminated intravascular coagulation in rats by inhibiting plasma thrombin and kallikrein [44]. On the other hand, several studies have reported that PCI physiologically inhibits plasma APC in vivo [45–48]. However, it is still unknown how PCI acts on the blood coagulation pathway in vivo .…”
Section: Discussionmentioning
confidence: 99%